Teretamon spelaeum, a new species of freshwater crab (Crustacea: Decapoda: Potamidae) from a limestone cave in Meghalaya, India - Absar, Parveen Farzana; Mitra, Santanu; Kharkongor, Ilona Jacinta (Zootaxa, 2017)
A new species of freshwater crab of the genus Teretamon Yeo & Ng, 2007 is described based on material collected from a limestone cave state of Meghalaya, in the northeastern Himalayan region of India. Teretamon spelaeum n. sp. can easily be distinguished from its congeners by a well suite of carapace and gonopod characters: a relatively wider carapace, setose chelipeds and legs, a highly reduced cornea of the eye, and a diagnostic male first gonopod that has a low rounded median dorsal flap on the terminal joint. The morphology of the new species is clearly adapted for the cave dwelling and is the first true troglobitic freshwater crab known from India.